Bioefficacy and persistent toxicity of newer insecticide against thrips, Pseudodendrothrips mori (Niwa) and leaf webber, Diaphania pulverulentalis (Hampson) in mulberry cultivation - Prety Rekha, Narzary; Manimegalai, S; Vinothkumar, B; Suganthi, A; Radha, P; Shanmugam, R; Thangamalar, A; Kousika, J (Plant Science Today, 2024)
Two field trials were conducted in two locations to assess new insecticide molecules' efficacy against thrips and leaf webber in the mulberry ecosystem. Results indicated that fipronil 5SC @ 50 g a.i. /ha showed the highest percentage reduction in the population of thrips (87.13 and 88.41 % in the first and second trials, respectively) over untreated control. In contrast, for leaf webber, flubendiamide 39.35 SC @ 48 g a.i./ha showed the highest effectiveness with 85.56 and 89.90 per cent reduction over control in the first and second trials, respectively. Persistence was observed through laboratory bioassay. Results revealed that the order of persistent toxicity of insecticides against thrips based on persistent toxicity index was fipronil 5 SC > spinetoram 11.7 SC > thiacloprid 21.7 SC > dimethoate 30 EC. Emamectin benzoate 5SC and dimethoate 30 EC recorded the shortest persistency of 10 days after treatment against mulberry leaf Webber, while chlorantraniliprole 18.5 SC and flubendiamide 39.35 SC registered the longest persistency of 25 and 20 days, respectively at the recommended dose. Higher concentrations of pest–resistant proteins and enzymes were recorded in the insecticide-treated mulberry plants than in the untreated plants. To conclude, fipronil 5 SC and thiacloprid 21.7 SC were the most effective in checking the population of thrips. At the same time, emamectin benzoate 5SC and flubendiamide 39.35 SC were most efficient against leaf webber, besides having less persistent toxicity than other treatments. Hence, these insecticides may be recommended to manage thrips and leaf webber in the mulberry ecosystem.